ИСПОЛЬЗОВАНИЕ ВИДЕОМАТЕРИАЛОВ КАК СРЕДСТВА ФОРМИРОВАНИЯ КОММУНИКАТИВНОЙ КОМПЕТЕНТНОСТИ В ПРОЦЕССЕ ОБУЧЕНИЯ РУССКОМУ ЯЗЫКУ КАК ИНОСТРАННОМУ (Philological Studies, 2019)
: The paper considers the concept of communicative competence and demonstrates the suitability of using videos at the classes of Russian as a foreign language as one of the techniques contributing to the successful formation of foreign students communicative competence.
Keywords: communicative competence, using videos at the classes of Russian as a foreign language